Islamophobia and Post-Conflict Dynamics Affecting the Moro Muslim Minority in Southern Philippines, 2020–2024 - Saputra, Rafli Adi; Hapsari, Renitha Dwi (Padjadjaran Journal of International Relations, 2026)
This study examines Islamophobia and the conflict dynamics experienced by the Moro Muslim minority in Southern Philippines during 2020–2024. The main issue is how anti-Muslim sentiment influence the post-Bangsamoro peace process. The research aims to analyze the interaction between political, security, and social factors driving discrimination and violence. The conceptual framework is based on securitization theory. The method applied is qualitative document analysis, covering reports from international human rights organizations, official government policies, and media coverage. Findings reveal that despite political progress through the Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), Islamophobia remains instrumentalized by certain actors to sustain threat narratives, hinder integration, and fuel horizontal tensions. The study recommends strengthening minority protection mechanisms and ensuring independent monitoring of policy implementation in BARMM.  Penelitian ini mengkaji Islamophobia dan dinamika konflik yang dialami minoritas Muslim Moro di Filipina Selatan pada periode 2020–2024. Permasalahan utama adalah bagaimana sentimen antiMuslim mempengaruhi proses perdamaian pasca-Perjanjian Bangsamoro. Penelitian ini bertujuan menganalisis interaksi antara faktor politik, keamanan, dan sosial yang memicu diskriminasi serta kekerasan. Kerangka konseptual yang digunakan adalah teori securitization. Metode penelitian yang diterapkan adalah studi kualitatif dengan analisis dokumen, meliputi laporan lembaga HAM internasional, kebijakan resmi pemerintah, dan pemberitaan media. Hasil penelitian menunjukkan bahwa meskipun terdapat kemajuan politik melalui Bangsamoro Autonomous Region in Muslim Mindanao (BARMM), Islamophobia tetap digunakan oleh aktor tertentu untuk mempertahankan narasi ancaman, menghambat integrasi, dan memicu ketegangan horizontal. Rekomendasi penelitian ini menekankan perlunya penguatan mekanisme perlindungan minoritas dan pengawasan independen terhadap implementasi kebijakan di BARMM.